The Urgency of Reconstructing the National Inheritance Law System for the Protection of Adopted Children - Maulana, Martono; Sugianto, Sugianto; Azis, Abdul (JURNAL AKTA, 2025)
The main issue in Indonesia's national inheritance law system lies in the lack of recognition of adopted children as legitimate heirs in the absence of a will, as stipulated in Article 832 of the Indonesian Civil Code (KUHPerdata), which limits inheritance rights exclusively to blood relatives. This provision creates significant inequality and discrimination against adopted children, as they are legally excluded from inheritance rights unless granted through a testamentary gift a mechanism that is limited in amount and not automatically applied. This study aims to examine the urgency of reconstructing the national inheritance law system to ensure equal legal protection for adopted children. The research employs a normative legal method, using both normative juridical and conceptual approaches. The findings reveal a legal vacuum (rechtsvacuum) and a juridical gap between existing positive legal norms and the principles of human rights and child protection. The current national inheritance system fails to provide adequate legal recognition of adopted children as part of the family in the context of inheritance. Therefore, a reconstruction of the national inheritance law is necessary one that incorporates the principles of caregiving and child welfare as the basis for recognizing family relationships, rather than relying solely on biological ties. Strategic approaches may include the addition of new norms to the Civil Code or the enactment of a National Inheritance Law that explicitly acknowledges the inheritance rights of adopted children. In addition, such inheritance law reform must be supported by strengthening protective mechanisms through the judicial system and social institutions, ensuring that adopted children can obtain legal certainty, substantive justice, and equal treatment before the law.